View point on hydrothermal sintering: Main features, today's recent advances and tomorrow's promises. (1st January 2019) - Goglio, Graziella; Ndayishimiye, Arnaud; Largeteau, Alain; Elissalde, Catherine
Abstract: The development of new high performance materials faces the challenge of implementing low temperature densification processes to overcome current technological limitations. In this context, the hydrothermal sintering, inspired by the natural processes of geological and biological mineralization, has recently emerged as a major opportunity to develop new and/or optimized materials that respond to today's scientific, technological and related socio-economic issues. The purpose of this viewpoint paper is to present opinions and propose future outlook for hydrothermal sintering based on the most recent achievements. Graphical abstract: Unlabelled Image